Enhanced settling of fine silica by direct AC electrocoagulation. (1st September 2013) - Ifill, R. O.; Etsell, T. H.
Abstract : Ground silica ( d 50, 20 μm) was treated as an aqueous suspension of 5·0 wt-% solids by alternating current electrocoagulation (AC/EC) in the direct mode. The initial settling rate increased linearly by 0·054 m h −1 per minute of AC/EC, with the maximum (>7·32 m h −1 ) occurring at t >120 min of AC/EC. Up to 75 min, floc size controlled the initial settling rate; at longer times, floc morphology took control. Aluminium released from the electrodes was adsorbed as it entered the pulp, and could be viewed as having been metered in continuously. Aluminium precipitation became prominent after ∼75 min of AC/EC time and was not deleterious to the enhancement of settling behaviour. Two years after its preparation, electrocoagulated silica was demonstrated to be an effective coagulant for as-received silica and oil sands fluid fine tailings.